UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PKn DENGAN METODE ‘TATAS’ PADA SISWA KELAS VIII-3 SMP NEGERI 2 MUARA TAHUN PELAJARAN 2019/2020 - Enda Hutabarat (Universitas Negeri Medan, 2020)
Abstract: Efforts to Improve Motivation and Learning Outcomes of Pkn with the 'Tatas' Method in Class Viii-3 Junior High School 2 Muara Students in 2019/2020 Academic Year. The purpose of this classroom action research is to increase the motivation and learning outcomes of Civics class VIII-3 students using the